FAM3C Regulates Glioma Cell Proliferation, Invasion, Apoptosis, and Epithelial Mesenchymal Transition via the Notch Pathway - Xiaochao Xia; Zihao Wang; Lvmeng Song; Yinchuan Cheng; Ping Xiong; Shun Li (Cancer Medicine)
ABSTRACT Background Previous studies have implicated the involvement of FAM3C in cancerous development and progression. Herein, we aimed to further investigate the oncological mechanism of FAM3C, specifically in glioma. Methods We utilized open‐source bioinformatics tools and platforms to analyze the transcriptional expression levels, prognosis, and correlation with clinical variables of FAM3C in gliomas, and subsequently, to hypothesize its potential molecular functions and possibly associated signaling pathways. Following this, glioma tissues were obtained from resected specimens of patients to assess the expression of FAM3C and molecular markers related to epithelial–mesenchymal transition (EMT) and Notch signaling pathways. Furthermore, glioma cell lines were subjected to treatments including FAM3C siRNA knockdown, lentiviral overexpression, and Notch signaling pathway blockade, enabling the investigation of molecular functions of FAM3C in vitro, particularly in EMT and Notch signaling pathways, as well as its effects on cancer cell proliferation, cell cycle progression, apoptosis, and invasion, using assays such as MMT cell proliferation assay, transwell migration, and flow cytometry analysis. Finally, a mouse subcutaneous xenograft model was established to explore the integrative function of FAM3C in glioma growth in vivo. Results The expression level of FAM3C correlated with the progression of glioma grade and served as a prognostic indicator for poor patient outcomes. Subsequent experiments conducted on glioma cell lines, tumor tissues, and mouse models reinforced the close association of FAM3C with processes including glioma cell proliferation, cell cycle progression, apoptosis, and invasion. Additionally, it was observed that FAM3C is involved in the regulation of the Notch signaling pathway. Conclusions FAM3C emerges as a potential candidate for clinical detection and prognostic biomarker application. Its regulatory role in glioma cell proliferation, cell cycle progression, and modulation of epithelial–mesenchymal transition‐driven invasion and migration via the Notch signaling pathway implies its potential to unveil novel therapeutic targets for glioma treatment.